(untitled) (Bangladesh Journal of Botany, 2018)
A field experiment involving five organic formulations viz., cow urine, vermiwash, neem seed extract, fish wash normal water (control) and three levels of NPK viz., 50% recommended dose of fertilizer (RDF), 75% RDF and 100% RDF with total 15 treatment combinations in randomized complete block design with three replications was conducted at Varanasi during Kharif season (July-April) 2014-15 to evaluate the effect of different organic formulations and NPK fertilization on pigeonpea. Results showed that increasing level of NPK up to 100% RDF significantly improved growth parameters, yield attributes, grain and straw yield. Among the treatment combinations, combined application of 100% RDF + vermiwash proved superior over other treatments, these recorded the highest growth yield attributes, gross returns, and net returns while B : C ratio was the highest under 100% RDF in combination with cow urine.